Association of Brachial-Ankle Pulse Wave Velocity and Cardiomegaly With Aortic Arch Calcification in Patients on Hemodialysis. Issue 19 (May 2016) - Shin, Ming-Chen Paul; Lee, Mei-Yueh; Huang, Jiun-Chi; Tsai, Yi-Chun; Chen, Jui-Hsin; Chen, Szu-Chia; Chang, Jer-Ming; Chen, Hung-Chun
Abstract : Abstract: Aortic arch calcification (AoAC) is associated with cardiovascular and all-cause mortality in end-stage renal disease population. AoAC can be simply estimated with an AoAC score using plain chest radiography. The objective of this study is to evaluate the association of AoAC with brachial-ankle pulse wave velocity (baPWV) and cardiomegaly in patients who have undergoing hemodialysis (HD). We retrospectively determined AoAC and cardiothoracic ratio (CTR) by chest x-ray in 220 HD patients who underwent the measurement of baPWV. The values of baPWV were measured by an ankle-brachial index-form device. Multiple stepwise logistic regression analysis was used to identify the factors associated with AoAC score >4. Compared patients with AoAC score ≦4, patients with AoAC score >4 had older age, higher prevalence of diabetes and cerebrovascular disease, lower diastolic blood pressure, higher baPWV, higher CTR, higher prevalence of CTR ≧50%, lower total cholesterol, and lower creatinine level. After the multivariate stepwise logistic analysis, old age, cerebrovascular disease, high baPWV (per 100 cm/s, odds ratio [OR] 1.065, 95% confidence interval [CI] 1.003–1.129, P = 0.038), CTR (per 1%, OR 1.116, 95% CI 1.046–1.191, P = 0.001), and low total cholesterol level were independently associated with AoAC score >4. Our study demonstrated AoAC severity was associated with high baPWV and high CTR in patients with HD. Therefore, we suggest that evaluating AoAC on plain chest radiography may be a simple and inexpensive method for detecting arterial stiffness in HD patients.